2015
DOI: 10.15547/bjvm.870
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional treatments for endometritis in mares

Abstract: SummaryBuczkowska, J., R. Kozdrowski, M. Sikora, M. Dzięcioł & A. Matusz, 2015. Non-traditional treatments for endometritis in mares. Bulg. J. Vet. Med., 18, No. 4,[285][286][287][288][289][290][291][292][293] Routine treatment for persistent mating-induced endometritis is directed at enhancing the clearance of accumulated fluid from the uterus and includes the use of ecbolic agents (oxytocin, prostaglandin F 2a ) which may be used alone or in combination with large-volume uterine lavage and administering anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Las vías de administración, las dosis y el agente bacteriano entre otros factores influyen en la elección del protocolo antibiótico para el tratamiento de la endometritis en yeguas (7). Por lo tanto, el objetivo del presente estudio fue evaluar la eficacia clínica de tres protocolos antibióticos en yeguas con diagnóstico de endometritis bacteriana y verificar su desempeño reproductivo postratamiento.…”
Section: Introductionunclassified
“…Las vías de administración, las dosis y el agente bacteriano entre otros factores influyen en la elección del protocolo antibiótico para el tratamiento de la endometritis en yeguas (7). Por lo tanto, el objetivo del presente estudio fue evaluar la eficacia clínica de tres protocolos antibióticos en yeguas con diagnóstico de endometritis bacteriana y verificar su desempeño reproductivo postratamiento.…”
Section: Introductionunclassified
“…More commonly, antibiotics are used in mares (Ferris, 2017) to treat reproductive tract infections but with variable success rate. Treatment failure may be because of presence of uterine exudates, mucus or biofilm produced by some bacteria and yeast (Buczkowska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a mixed population of organisms, focal infections, highly pathogenic and biofilmproducing bacteria can also contribute to chronic inflammation and hinder findings during diagnostic exams such as microbiological culture and, consequently, antibiotic treatments. 13,27 Metagenomic studies revealed that a moderately diverse microbiome is also present in uterine samples, where no significant growth was obtained by conventional culture. 28 In addition, inadequate treatments and inefficient defense mechanisms leading to susceptibility can cause dysbiosis.…”
Section: Discussionmentioning
confidence: 99%